An enabling strategy for ultra-fast lithium storage derived from micro-flower-structured NiX (X=O, S, Se). (20th May 2020) - Wang, Lei; Wang, Zehua; Xie, Lingling; Zhu, Limin; Cao, Xiaoyu
Abstract: Transition metal oxides/sulfides/selenides (TMOSS), regarded as three of the most potential anode materials for lithium-ion batteries (LIBs), are superior to their low cost, controllable morphology and high theoretical capacity. Herein, a facile strategy, using Ni-MOF material as precursor, was designed to fabricate the unique micro-flower-like NiO, NiS/C and NiSe/C electrodes, including the detailed investigation about their electrochemical and kinetics properties. The results show that sizes of NiO, NiS/C and NiSe/C micro-flowers are around 0.7, 3.5 and 2.0 μm, respectively, which contains abundant micro- and meso-pores. Among them, NiSe/C material exhibits better electrochemical performance when used as anode electrode for LIBs, with high initial capacity (1688.4 mAh g −1 at 0.1 A g −1 ) and high reversible capacity (1016.5 mAh g −1 at 1.0 A g −1 after 1000 cycles). Moreover, the full-cell, NiSe/C vs . LiCoO2, exhibits superior reversible discharge capacities of 421.8 mAh g −1 at 0.1 A g −1 after 50 cycles. It is important that the bond energy of Ni–Se contributes to improving NiSe/C electrochemical performance. This work shows the influence of Li + insertion and pseudocapacitance behavior on lithium storage performance of TMOSS anode materials, which provides an effective strategy for research and development of TMOSS on LIBs. Graphical abstract: Image 1